2022
DOI: 10.1109/jphot.2022.3149348
|View full text |Cite
|
Sign up to set email alerts
|

SRS-Induced Spatial-Spectral Distortion and Its Mitigation Strategy in High-Power Fiber Amplifiers

Abstract: The spatial-spectral evolution properties of laser beam in the presence of stimulated Raman scattering (SRS) effect have been studied in large mode area (LMA) fiber. With the employment of long/short pass filters, spatial evolution of the signal and Raman light has been studied individually. After the onset of SRS, the simultaneous optimizing of signal light and degrading of Raman light was observed, which has been attributed to the SRS effect of multimode laser beams in LMA fiber. The spectral evolution chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This abnormal phenomenon has been observed in Ref. [34] To further identify the correlation between beam quality and SRS effect, Figure 7 compares the temporal characteristics at the maximum output power with three different pump conditions.…”
Section: Brightness Enhancement By Pump Ratio Optimzationmentioning
confidence: 54%
“…This abnormal phenomenon has been observed in Ref. [34] To further identify the correlation between beam quality and SRS effect, Figure 7 compares the temporal characteristics at the maximum output power with three different pump conditions.…”
Section: Brightness Enhancement By Pump Ratio Optimzationmentioning
confidence: 54%
“…The low absorption cross-section of Yb ions at the tandem pumping wavelength (e.g., 1018 nm) requires long gain fiber for adequate pump absorption, resulting in a relatively low SRS threshold. Additionally, recent studies have shown that SRS might trigger quasi-static mode distortion [6][7][8] or dynamic mode instability (MI) [9][10][11][12][13] , which could degrade the beam quality and directivity of the fiber laser systems. Therefore, mitigating SRS effect is crucial for tandem pumping towards higher power with good beam quality.…”
Section: Introductionmentioning
confidence: 99%
“…The SRS effect is physically described as the amplification of spontaneous Raman radiation caused by signal light pumping [4], leading to a decrease in signal power. Furthermore, the SRS effect can also deteriorate the beam quality due to the transverse mode instability (TMI) effect [5,6]. Therefore, effectively mitigating the SRS effect is crucial in the design of high-power single-mode fiber lasers.…”
Section: Introductionmentioning
confidence: 99%